Fitting curves to human respiratory data - Jacob, G; Marriott, F; Robbins, P (1997)
Records of gas flow during breathing are cyclical, with the cycles varying in duration. The shape of these cycles may change with the intensity of respiratory stimulation or the development of respiratory disease, but currently research is hampered by the lack of a fully satisfactory technique for determining the shape of a typical cycle. The approach adopted here is to replace the time series by a 'phase diagram', plotting the time integral of flow against flow itself. Principal curves are then fitted. These are curves 'through the middle of the data' which were introduced by Hastie and Stuetzle. The shapes of these curves are compared, either directly or after reconstructing an average cycle corresponding to each fitted curve. This has the advantage that the shape of the waveform is separated from the amplitude, and from the duration of the breath. A disadvantage is that periods of zero flow are lost, and the reconstructed average cycle may show irregularities at points near zero flow as a result. In practice, the methodology showed clear differences in shape between the protocols, gave reasonable average cycles and ordered the waveform shapes according to the hardness of breathing induced by the protocols.